2008
DOI: 10.1007/s00431-008-0710-5
|View full text |Cite
|
Sign up to set email alerts
|

ACTH-dependent precocious pseudopuberty in an infant with DAX1 gene mutation

Abstract: DAX1 gene (Xp21) expression is involved in the development of the hypothalamo-pituitary-gonadal and adrenal axes, and acts as a negative regulator of steroidogenesis. Mutations of this gene determine adrenal hypoplasia congenita (AHC) and hypogonadotropic hypogonadism. We report the case of a 9-month-old boy referred for the study of macrogenitosomia and pubic hair development. He had presented acute adrenal crises in the neonatal period and, later, a clinical picture of peripheral precocious puberty. A mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Indeed, GnRH analog treatment ameliorated the physical symptoms and laboratory findings in 3 cases [Darcan et al, 2011;Durmaz et al, 2013;Koh et al, 2013]. Alternatively, adrenocorticotropic hormone (ACTH) overproduction secondary to adrenal insufficiency may underlie PP in AHC patients, because it was reported that the clinical features of 2 patients were lessened during glucocorticoid supplementation therapy [Domenice et al, 2001;Yeste et al, 2009]. Consistent with this, ACTH was suggested to exert a stimulatory effect on steroid biosynthesis in the testis [O'Shaughnessy et al, 2003].…”
Section: Nr0b1 Frameshift Mutation In a Boy With Idiopathic Central Pmentioning
confidence: 55%
See 1 more Smart Citation
“…Indeed, GnRH analog treatment ameliorated the physical symptoms and laboratory findings in 3 cases [Darcan et al, 2011;Durmaz et al, 2013;Koh et al, 2013]. Alternatively, adrenocorticotropic hormone (ACTH) overproduction secondary to adrenal insufficiency may underlie PP in AHC patients, because it was reported that the clinical features of 2 patients were lessened during glucocorticoid supplementation therapy [Domenice et al, 2001;Yeste et al, 2009]. Consistent with this, ACTH was suggested to exert a stimulatory effect on steroid biosynthesis in the testis [O'Shaughnessy et al, 2003].…”
Section: Nr0b1 Frameshift Mutation In a Boy With Idiopathic Central Pmentioning
confidence: 55%
“…Previous studies have shown that patients with AHC occasionally manifest early sexual maturation ( table 1 ) [Takahashi et al, 1997;Domenice et al, 2001;Argente et al, 2003;Ahmad et al, 2007;Loke et al, 2009;Yeste et al, 2009;Landau et al, 2010;Darcan et al, 2011;Durmaz et al, 2013;Koh et al, 2013]. Phenotypic severities of these patients vary from PP with pubic hair and advanced bone age to transient testicular/penile enlargement without additional symptoms.…”
Section: Nr0b1 Frameshift Mutation In a Boy With Idiopathic Central Pmentioning
confidence: 99%
“…However, some affected boys might develop pubertal sign up to Tanner stage 3, when puberty stops due to disrupted hypothalamic and pituitary release of gonadotropin-releasing hormone and gonadotropins, respectively (6). Similarly, a few patients with DAX-1 mutation were reported to develop ACTH-dependent transient precocious pseudopuberty during infancy/childhood (7,8).…”
Section: Dax-1encodes An Orphan Nuclear Hormone Receptor and Interactmentioning
confidence: 99%
“…To date, hundreds of different mutations in NR0B1 have been reported, including deletions, frameshift, and point mutations, with variable onsets of presentation, different degrees of mineralocorticoid and glucocorticoid insufficiency, hypogonadism, and in some instances precocious puberty. A clear genotype–phenotype correlation is yet to be defined …”
Section: Introductionmentioning
confidence: 99%